Changes of peripheral T cell subsets in melanoma patients with immune-related adverse events - Müller, Benjamin; Bärenwaldt, Anne; Herzig, Petra; Zippelius, Alfred; Maul, Lara Valeska; Hess, Viviane; König, David; Läubli, Heinz (Frontiers in Immunology, 2023)
Immunotherapies have improved the prognosis of many cancer patients including patients with advanced melanoma. Immune checkpoint receptors including CTLA-4 and PD-1 have been established as main therapeutic targets for immunotherapy of melanoma. Although monotherapy is effective in melanoma patients, a dual therapy approach has been shown to be most effective. Dual checkpoint blockade, however, increases substantially the risk for immune-related adverse events (irAEs). In this study, we characterized peripheral immune cell subsets in patients with anti-PD-1 monotherapy and with dual immune receptors blockade targeting PD-1 and CTLA-4. We found differences in peripheral T cells between patients who developed severe immune-related side effects and patients with mild irAEs. We identified several mainly changes in CD8+ T cell subsets in patients with severe irAE under dual PD-1 and CTLA-4 blockade. This work suggests that peripheral immune cell dynamics could be associated with severe immune-related side effects in patients receiving immune checkpoint inhibitors. These changes could be used as future biomarkers in early diagnosis of irAEs.